Water‐Enabled Electricity Generation: A Perspective. Issue 4 (7th February 2022) - Zhao, Xiaoye; Shen, Daozhi; Duley, Walter W.; Tan, Caiwang; Zhou, Y. Norman
Abstract : Harvesting energy from the environment offers many opportunities for the generation of clean power from self‐sustained systems and provides great promise for ameliorating the growing threat of the global environmental issues and the energy crisis. Ambient moisture and natural water sources have attracted huge research interest in the field of energy harvesting and conversion due to easy access, good sustainability, and the ubiquity of water on Earth. Taking advantage of the active interaction between water molecules and solid interfaces, various functional materials have been demonstrated to harvest energy and generate useable amounts of electrical power from water. In this review, some perspective on the development of water‐enabled electricity generation is given. The current preferred methods for water‐enabled electricity generation and relevant functional materials are summarized. Also, how the development of new materials and systems has led to significant improvements in the electrical power output reported for these devices is discussed. Then, some recent advances that have resulted in dramatic increases in the electrical output available from water‐enabled electrical generators (WEEGs) is discussed. Finally, some future trends in the development of WEEGs are outlined, and how this may result in practical applications and commercialization of these devices is shown. Abstract : Water‐enabled electricity generators (WEEGs) show good promise in the fields of green energy sources, novel battery‐free biosensors, and wearable electronics. Herein, the development of energy conversion materials and applications of WEEGs is reviewed in detail, suggesting remaining challenges and future directions and opportunities of WEEG.